Development and preliminary validation of the Salzburg Stress Eating Scale. (1st January 2018) - Meule, Adrian; Reichenberger, Julia; Blechert, Jens
Abstract: Stress-related eating has long been a focus of study in several disciplines. Currently available psychometric scales conflate stress-related eating with emotional eating despite that not all stress states can be subsumed under some form of specific emotion. Moreover, existing measures primarily assess increased food intake in response to emotions and stress, thus ignoring evidence of decreased food intake in response to stress. Therefore, we drew from established stress concepts to develop the first genuine stress-related eating scale (Salzburg Stress Eating Scale [SSES]) in both German and English versions. In the SSES higher scores indicate eating more when stressed and lower scores indicate eating less when stressed. In study 1 ( n  = 340), the German SSES was found to have a one-factor structure (α = 0.89). SSES scores were weakly or moderately correlated with other eating-related constructs (e.g., emotional eating, body mass index [BMI]), and weakly correlated or uncorrelated with non-eating-related constructs (e.g., impulsivity, perceived stress); in addition, women had higher scores than men. Perceived stress moderated the association between stress eating and BMI, such that higher SSES scores were significantly related to higher BMI in individuals with high perceived stress, but not in individuals with low perceived stress. In studies 2 ( n  = 790) and 3 ( n  = 331), factor structure, internal consistency, and associations with sex and BMI were replicated for both German and English versions of the SSES. Hence, the SSES represents a psychometrically sound tool for the measurement of stress-related eating.